Mapping the serum proteome to neurological diseases using whole genome sequencing - Grace Png (Nature Portfolio, 2021)
Serum proteins are easily accessible biomarkers and drug targets. Here, the authors use whole genome sequencing data to describe the genetic architecture of neurologically-relevant serum proteins and establish causal protein-neurological disease relationships.